Pathologic T1 and T2 encapsulated invasive carcinomas arising from mucinous cystic neoplasms of the pancreas have favorable prognosis and might be treated conservatively - Huaiyu Liang; Wen Xie; Xiaozhu Lin; Ting Wang; Jing Xie; Chaofu Wang; Shu‐Yuan Xiao; Yan Guo (Wiley, 2021)
Abstract Carcinoma arising from a mucinous cystic neoplasm (MCN) of the pancreas is termed MCN with associated invasive carcinoma (MCN‐AIC) in the fifth WHO classification of digestive tumors (2019). The prognosis of this malignancy varies depending on the relationship of the invasive carcinoma to the cyst capsule, but limited data are available. This study identified 165 surgically resected MCNs including 15 MCN‐AICs from a single center between 2008 and 2018 and analyzed their clinicopathologic features. The results confirmed that non‐invasive MCNs were completely cured by surgery. All MCN‐AICs showing an encapsulated invasion pattern (defined as invasive carcinoma limited to the ovarian‐type stroma, cystic septa, and capsule) had an excellent prognosis with a 5‐year survival rate of 100%, even when the size of the invasive component was up to stage T2. By contrast, MCN‐AICs with extracapsular involvement had unfavorable clinical outcomes. Our study demonstrates that the pattern of invasion of MCN‐AIC can predict patient prognosis. Pathologic stage T1 and T2 encapsulated MCN‐AICs may be completely cured with surgical resection alone or when combined with postoperative chemotherapy.